The Effect of Other People's Recommendations and Social Media Facilities on Purchase Interest - Tanty Sondari; Epa Nopianti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
Technological developments can make it easier for consumers to give an assessment or review of the products they buy and the results of these reviews can influence consumers to be interested or not buy, buying products after knowing information from consumers directly or indirectly through online reviews. This study aims to determine other people's recommendations and social media facilities on the interest in buying a CV. Consina Sagara Alam backpack product. As well as to determine the magnitude of the influence of other people's recommendations and social media facilities on the interest in buying backpack products on a CV. Consina Sagara Alam. The research method used is descriptive and verification with a sample of 100 respondents. Data collection techniques used are observation questionnaires and literature studies. The statistical analysis method used is path analysis with partial hypothesis testing (t-test) and simultaneously (f-test). The results of the t-test show that there is a significant positive effect between other people's recommendations and purchase interest and there is a significant positive effect between social media facilities and purchase interest. While the results of the f-test showed that there was a significant influence between other people's recommendations and social media facilities on purchase interest.